The Influence of Unemployment on Poverty in the City of Bandung - Marbun, Sonia Hapsari; Aadilah, Hilmi; Lubis, Ahmad Rahman Hamdani; Dongoran, Faisal Rahman (PT. Riset Press International, 2023)
A This study aims to find out whether unemployment affects the condition of poverty in the city of Bandung in 2017-2021 and how does the variable unemployment affect it. The research uses quantitative research methods by processing data using the Eviews application. Research data comes from the Central Bureau of Statistics (BPS). Based on the results of data processing, it is known that unemployment does not have a significant and partial effect on poverty in the city of Bandung in 2017-2021. This is evidenced by the probability value of the t-statistic below 0.05%. In addition, based on the Adjusted R-squared value, it is known that although there is no unemployment, there are other indicators that affect poverty in the city of Bandung.